Impact of the reduction of calcineurin inhibitors on renal function in heart transplant patients: a systematic review and meta-analysis - Cornu, Catherine; Gleißner, Christian A. (British journal of clinical pharmacology, 2014)
Aims: Calcineurin inhibitors (CNIs) taken after heart transplantation lead to excellent short-term outcomes, but long-term use may cause chronic nephrotoxicity. Our aim was to identify, appraise, select and analyse all high-quality research evidence relevant to the question of the clinical impact of CNI-sparing strategies in heart transplant patients. Methods: We carried out a systematic review and meta-analysis of randomized controlled trials on CNI reduction in heart transplant recipients. Primary outcomes were kidney function and acute rejection after 1 year. Secondary outcomes included graft loss, all-cause mortality and adverse events. Results: Eight open-label studies were included, with 723 patients (four tested de novo CNI reduction and four maintenance CNI reduction). Calcineurin inhibitor reduction did not improve creatinine clearance at 12 months 5.46 [−1.17, 12.03] P = 0.32 I2 = 65.4%. Acute rejection at 12 months (55/360 vs. 52/332), mortality (18/301 vs. 15/270) and adverse event rates (55/294 vs. 52/281) did not differ between the low-CNI and standard-CNI groups. There was significant benefit on creatinine clearance in patients with impaired renal function at 6 months [+12.23 (+5.26, +18.82) ml min−1, P = 0.0003] and at 12 months 4.63 [−4.55, 13.82] P = 0.32 I2 = 75%. Conclusions: This meta-analysis did not demonstrate a favourable effect of CNI reduction on kidney function, but there was no increase in acute rejection. To provide a better analysis of the influence of CNI reduction patterns and associated treatments, a meta-analysis of individual patient data should be performed.
Accepted article published online: 20 November 2013
Gesehen am 23.09.2020